The Analysis of Swearwords Used in Buleleng - Tanjung, K. Senaputra (Journal of Educational Study, 2024)
This study aims to analyze the use of swear words in the Balinese language used by the people in Buleleng Regency, North Bali. Using a descriptive qualitative approach, this study explores the forms, references, and functions of swear words commonly used in everyday social interactions. According to Anderson & Trudgill (1990), swear words refer to something taboo in certain cultures and are used to express strong emotions or attitudes. Robin (1992) adds that swear words are often used to convey anger or passion. Hughes (1998) classifies swear words based on their types, such as those related to sexuality, filth, and animal names. In Buleleng, words such as pirata (ancestor), naskleng (male genitalia), tai (excrement), cicing (dog), and lengeh (stupid) are commonly used, even by children, as part of a long-standing cultural heritage. The use of these words is not always negative but can also serve to attract attention, alleviate discomfort, provoke, create interpersonal identity, and function as both integrative and aggressive expressions. These findings suggest that swear words in Buleleng play a significant role in social communication and reflect the dynamics of local culture.